A Romantic Spirit in Priangan - Setiawan, H.W.; Sabana, Setiawan (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Java, where the VOC (Verenigde Oost-Indische Compagnie or East Hindia-Dutch Company) â later a colonial state â established its base, was undoubtedly one of the most important regions in East Indies, which attracted colonial era of Europeans, not to mention those who relied on visual images, especially in 19th century. It was the age when revolution broke out in Europe and liberal thoughts paved the way for private companies to open business in the colony, resulting various writings and drawings made by Europeans, especially the Dutch and British, on the East Indies, especially Java. This essay discusses three interrelated subjects in the history of European visual representation of Dutch East Indies (the present day Indonesia). Firstly, the attractiveness of East Indies, especially Java, as Dutch colony in Asia, for 19th century European society as could be seen from innumerable pictures and travelogues on the region and world-class exhibitions on the subject, in both the Netherlands and France, which displayed various aspects of the land and people. Secondly, the significance of Priangan, a mountainous region in western part of Java, in the eyes of 19th century European, who traveled and conducted scientific investigations in the region so that the mountain region became a subject of various images and narratives. Thirdly, the role of Franz Wilhelm Junghuhn (1809-1864), probably the most important researcher and explorer of Java at the time, in the production of visual images and travelogues of the land.KEY WORDS: Dutch East Indies, Java island, Franz Wilhelm Junghuhn, history, Priangan, European society, and visual representation.Â Â About the Authors: H.W. Setiawan is a Postgraduate Student of Doctoral Programme at the Faculty of Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10 Tamansari, Bandung, West Java, Indonesia; and Prof. Dr. Setiawan Sabana is a Lecturer at the Faculty of Art and Design ITB. For academic interests, the authors are able to be contacted via e-mails at: hawesetiawan@unpas.ac.id and setiawansabana@yahoo.comHow to cite this article? Setiawan, H.W. & Setiawan Sabana. (2015). âA Romantic Spirit in Prianganâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.139-148. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (September 22, 2014); Revised (December 29, 2014); and Published (April 28, 2015).